Study on thermal health and its safety management mode for the working environment - Jue Wang; Jue Wang; Jue Wang; Cheng Jiang; Guang Yang; Gang Bai; Gang Bai; Shixuan Yu (Frontiers Media S.A., 2023)
Thermal health concerns have gained significant attention due to the heightened health risks faced by workers who are exposed to extreme thermal environments for prolonged periods. To ensure the occupational health and safety of such workers, and to enhance work efficiency, it is imperative to examine the characteristics of thermal health in the working environment. This study proposes three key elements of thermal health in the working environment, namely thermal health states, absence of heat-related illnesses, and heat adaptability, which can be used to develop a safety management framework for thermal health. By exploring the interconnections between these elements, the study summarizes their features and outlines the necessary precautions to safeguard them. The PDCA (plan/do/check/action) cycle management mode is utilized as a framework, with the three components of thermal health forming the core, to establish a safety management mode for thermal health. To ensure that employees work in a safe, healthy, comfortable, and productive environment, the assessment and control objectives of the thermal environment are regularly revised through the use of labor protection technology and thermal environment control technology. This paper presents a PDCA cycle safety management mode based on the characteristics of thermal health, which offers novel insights and approaches for assessing and managing workers' thermal health.